Visual storytelling : inspiring a new visual language. - Klanten, Robert; Losowsky, Andrew; Schulze, Floyd (Berlin : Gestalten, 2011)
Visual storytelling uses graphic design, infographics, illustration, and photography to convey information in the most elegant, entertaining, and informative way. Today, the creative scope of existing visual storytelling techniques is being expanded to meet the formidable challenge of extracting valuable news, surprising findings, and relevant stories from a daily flood of data head on. Visual Storytelling is the first book to focus solely on contemporary and experimental manifestations of visual forms that can be classified as such. The rich selection of cutting-edge examples featured here is put into context with an introduction and text features by magazine expert Andrew Losowsky as well as interviews with the New York Times, Francesco Franchi, Density Design, Carl Kleiner, Antoine Corbineau, Golden Section Graphics, Les Graphiquants, and Peter Grundy. The inspiring, insightful, interactive, and entertaining work and texts collected in Visual Storytelling reveal how the contextualization of information is pushing the envelope of today’s design and aesthetics.
boek